Enterovirus infections in early childhood and the risk of atopic disease – a nested case‐control study. Issue 6 (28th May 2013) - Korhonen, L.; Kondrashova, A.; Tauriainen, S.; Haapala, A. M.; Huhtala, H.; Ilonen, J.; Simell, O.; Knip, M.; Lönnrot, M.; Hyöty, H.
Summary: Background: Enterovirus infections in childhood have been associated with a reduced risk of atopy in cross‐sectional studies. Objective: To study the relation between enterovirus infections in the first 2 years of life and atopic disease with IgE sensitization in a prospective study setting. Methods: This was a nested case‐control study among children who had been followed from birth. Neutralizing antibodies against 12 enterovirus serotypes were analysed at the age of 2 years from 71 atopic children and 142 non‐atopic control children. Atopy was defined as having an atopic disease and IgE antibodies against at least one aeroallergen by the age of 5 years. Results: Cumulative exposure to different enterovirus serotypes was inversely associated with atopy [odds ratio (OR) 0.73; 95% confidence interval (CI): 0.56‐0.96]. The most pronounced protection was seen when echoviruses were analysed as a separate group (OR 0.63; 95%CI: 0.46–0.88). Conclusions and Clinical Relevance: We propose that exposure to several different enteroviruses in early childhood is inversely associated with atopic diseases. Our results support the hypothesis that repeated microbial infections in early life may protect from atopic sensitization and atopic diseases.